The micro-, submicron-, and nanoplastic hunt: A review of detection methods for plastic particles. (April 2022) - Caldwell, Jessica; Taladriz-Blanco, Patricia; Lehner, Roman; Lubskyy, Andriy; Ortuso, Roberto Diego; Rothen-Rutishauser, Barbara; Petri-Fink, Alke
Abstract: Plastic particle pollution has been shown to be almost completely ubiquitous within our surrounding environment. This ubiquity in combination with a variety of unique properties ( e.g. density, hydrophobicity, surface functionalization, particle shape and size, transition temperatures, and mechanical properties) and the ever-increasing levels of plastic production and use has begun to garner heightened levels of interest within the scientific community. However, as a result of these properties, plastic particles are often reported to be challenging to study in complex ( i.e. real) environments. Therefore, this review aims to summarize research generated on multiple facets of the micro- and nanoplastics field; ranging from size and shape definitions to detection and characterization techniques to generating reference particles; in order to provide a more complete understanding of the current strategies for the analysis of plastic particles. This information is then used to provide generalized recommendations for researchers to consider as they attempt to study plastics in analytically complex environments; including method validation using reference particles obtained via the presented creation methods, encouraging efforts towards method standardization through the reporting of all technical details utilized in a study, and providing analytical pathway recommendations depending upon the exact knowledge desired and samples being studied. Graphical abstract: Image 1 Highlights: Summarizes key terms and analytical techniques for plastic particle research. Highlights new, promising analytical techniques for plastic particle studies. Proposes strategies for standardizing and improving the analytical pathway for plastics.